Calculation of the Effect of Substation Configuration on the Resistance Value of the Grounding System - Ayu Fitriani; Jhoni Hidayat; Joel Panjaitan; Syofyan Anwar Syahputra; Mili Alfisari (Journal of Renewable Energy, Electrical, and Computer Engineering, 2025)
Generally, the configuration of the substation grounding system is in the form of a grid or mesh, where several conductor rods are installed vertically and horizontally or combined with conductor rods planted deep in the ground from each point or not. The substation configuration is very complex because of the many variables used in accordance with IEEE Standard 80-2013. This variable also influences the allowable and actual magnitude of the step voltage and touch voltage. The substation grounding system configuration can be designed in several shapes including rectangular, square, L-shaped and T-shaped. The parameters used are an area of 70 m x 70 m, a conductor rod depth of 0.5 meters with a total conductor length for a rectangle of 1540 meters without rods, an L-Shaped shape of 1755 meters and a T-Shaped shape of 3857 meters. The results obtained by the resistance of the grounding system without rods in the T-Shaped configuration were 2.39 Î©. For the resistance results, the grounding system uses a rod with the same area and a conductor length of 3917 meters with a resistance value of 2.39 Î© in the T-shape configuration. The results of the resistance values obtained with various forms of grounding system configurations and varying conductor lengths are still safe and below the threshold or standard of the grid grounding system.